CHRISTIANITY IN GEORGIAN-RUSSIAN RELATIONS: THEN AND NOW - PANJIKIDZE, Teimuraz (CENTRAL ASIA AND THE CAUCASUS, 2005)
Georgia and Russia: this is the order in which the issue should be discussed in conformity with the age of their statehoods and Chris tian Churches; Russia and Georgia: this is the or der in which they should be discussed in conformity with the territories and might of these two Chris tian Orthodox states. They have accumulated over 200 years of experience in joint statehood. They joined their fates at the time when Christian Orthodoxy was their only ideology. Religion was not the only factor that brought Russia and Georgia together—yet it was the mag net that pulled Georgia. Christianity was more than a faith in Georgia: it was its philosophy, its way of life, and its shield. It was Christianity that defend ed the state for many centuries against the inroads of numerous enemies who came to impose their religions on us. At all times, Christianity reminded the Georgians that they should preserve their tongue, their national character, and their specific features in order to remain Georgians. We have survived thanks to our Christian faith. The above sounds bombastic, yet it is absolutely true, even though I deliberately suppressed certain facts… At one time, great Georgian writer Ilia Chavchavadze wrote: “For us Christianity is more than living according to Christ: it means our Motherland, Georgia; it means that we are Georgians. Today, the whole of the Transcaucasia makes no distinction between Georgians and Christianity—they are one and the same thing. Instead of saying that someone became a Christian, they say, he became a Georgian. Our clergy knew only too well that the Fatherland and nationality, united by faith and conjoined with it, are an invincible weapon and shield in the face of the enemy. All sermons were designed to uplift the meaning of Fatherland and nationality to the height of faith so that all people might serve these three intertwined, sacred, and great objects with the utmost dedication.” 1 All of a sudden, however, Christian ideology, this mighty battle-tested weapon which helped the Georgians remain loyal to their faith and not succumb to the Turks and Mongols, lost its power. This happened when the Georgians’ interests clashed with the same religion, with another Christian Orthodox people who initially, it seemed, wanted to help them. I have in mind our relations with Chris tian Orthodox Russia, that is, the “common faith” factor. Indeed, Georgia and Russia shared the same faith and the same Christian values. At that time, Christians of the same confession sought closer contacts in their opposition to the Muslim countries. Obviously “rapprochement” based on shared faith was tempting and ideologically justified, especially if one of the countries was surrounded by followers of different religions. The term “common faith” was not limited to Russia alone. It was also applied to Byzantium, with which Georgia maintained active contacts. In 1453, Constantinople fell, and Byzantium disappeared, leaving Russia the only country of the same faith and real might to which Georgia might turn for help in times of trial. Religion was not the main factor, yet it certainly played an important role. Academician N. Berdzenishvili said that the Georgians saw “a new Byzantium in Christian Russia. They expected this force to help them overcome the Muslim aggressors (Iran and Tur key) and restore their country’s old glory.” 2 Russia, which claimed the title of the Third Rome, treated Christianity as a handy instrument and ideological screen which did little to conceal its state interests.